DIMENSIONS OF LEADERSHIP BEHAVIORS DETERMINING ORGANIZATIONAL PERFORMANCE IMPROVEMENT - Andri, Andri; Hermawan, Aji; Sukmawati, Anggraini (Universitas Brawijaya, Indonesia, 2019)
This research has several purposes such as analyze the effect of leadership behaviour’s factors on organizational performance and analyze the right leadership behaviour which is proper to apply in organizational performance’s improvement at Palm Oil Mill (POM) Sei Galuh PTVN V, Kampar, Riau. This research used the explanatory survey as research design and purposive sampling as technique sampling from 60 respondents. The purpose of that survey is to measure the leadership behaviour at POM Sei Galuh PTPN V. Questionnaire of this research adopted from three-dimensional leadership model by Yukl. Multiple regression used as the method. Data processed and analyzed using SPSS 24.The result shows that task oriented leadership duty, relationship and change’s behaviour have a stimulant effect on organizational performance. Partially, task oriented leadershipbehaviour has no significant effect, relationship orientedleadership behaviour has a positive and significant effect, and change oriented leadership behaviour has a negative and significant on organizational performance. Future research was expecting to complete this research with qualitative data through in-depth interview and focusing on doing some discussion with staffs starting from operator until top management.